2018
DOI: 10.4314/ovj.v8i2.1
|View full text |Cite
|
Sign up to set email alerts
|

Indolent, T-cell, large granular lymphocytic leukaemia in a dog presenting with severe neutropenia and an absence of lymphocytosis

Abstract: In humans, large granular lymphocytic leukaemia (LGLL) is a low-grade, indolent lymphoproliferative disorder of large granular lymphocytes (LGL) associated with autoimmune disorders; including rheumatoid arthritis and single or multiple cytopenias; particularly neutropenia. Therapy largely centres around immunosuppression which aims to resolve the immune-mediated secondary pathology, often without eradicating the neoplastic clone. The most effective agents appear to be cyclophosphamide, cyclosporine and methot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
1
0
1
Order By: Relevance
“…Review of previously reported cases reveals a mean age of 9 years (range 4-14) across 41 cases. 5,14,[16][17][18][19][20][21][22][23] Across these previous publications, a male to female ratio of 0.7:1 was identified in contrast to the current study where male dominance was identified.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Review of previously reported cases reveals a mean age of 9 years (range 4-14) across 41 cases. 5,14,[16][17][18][19][20][21][22][23] Across these previous publications, a male to female ratio of 0.7:1 was identified in contrast to the current study where male dominance was identified.…”
Section: Discussioncontrasting
confidence: 71%
“…Across the previous canine case reports, anaemia was identified in 56% of cases, neutrophilia in 49% of cases, thrombocytopaenia in 25% of cases and neutropenia in 17% of cases (some cases exhibited more than one cytopaenia). 5,14,[16][17][18][19][20][21][22][23] In comparison with the current study, these previously reported cases exhibited anaemia at nearly three times the occurrence and thrombocytopaenia at nearly two times the occurrence, while the incidence of neutrophilia was similar.…”
Section: Discussionsupporting
confidence: 54%